2018
DOI: 10.1016/j.landusepol.2018.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers’ motivations for providing unsubsidised environmental benefits

Abstract: This paper examines farmers' motivations for voluntary unsubsidised practices that benefit the environment. It identifies amongst a group of English farmers the amount of unsubsidised environmental activities on mainly arable land, and explores the extent to which motivations are extrinsic and intrinsic for undertaking this unsubsidised activity. Using responses from a national survey in England of 1,345 farmers, in-depth face-to-face interviews with 60 farmers and an analysis of existing agri-environment sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 49 publications
4
53
1
Order By: Relevance
“…An important contribution of this study to the current literature is the identification and inclusion of the factors Time horizon and Spatial horizon, as the perception of farmers regarding these two factors has not been included in previous studies, although diffuse pollution is known to be 'invisible' to farmers, which affects their motivation to act upon it (Macgregor and Warren 2006). These factors are likely to be less relevant to the adoption of environmental practices that have visible outcomes, such as conservation efforts or biodiversity practices (de Snoo et al 2013;Mills et al 2018;Truelove et al 2014;Van Herzele et al 2013), but will be more relevant for practices that have seemingly distant effects (both in time and space) such as climate change (Geoghegan and Leyson 2012). The results of our study imply that communication on nitrate leaching practices needs to be tailored for farmers with short time and space horizons.…”
Section: Factors Influencing Farmer Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…An important contribution of this study to the current literature is the identification and inclusion of the factors Time horizon and Spatial horizon, as the perception of farmers regarding these two factors has not been included in previous studies, although diffuse pollution is known to be 'invisible' to farmers, which affects their motivation to act upon it (Macgregor and Warren 2006). These factors are likely to be less relevant to the adoption of environmental practices that have visible outcomes, such as conservation efforts or biodiversity practices (de Snoo et al 2013;Mills et al 2018;Truelove et al 2014;Van Herzele et al 2013), but will be more relevant for practices that have seemingly distant effects (both in time and space) such as climate change (Geoghegan and Leyson 2012). The results of our study imply that communication on nitrate leaching practices needs to be tailored for farmers with short time and space horizons.…”
Section: Factors Influencing Farmer Decision-makingmentioning
confidence: 99%
“…Considering the limited financial resources compared with the Perpetuate Cooperates it might be important for the Enthusiasts to create a good fit with current management practices by focusing on how to combine financial and environmental aspects in best management practice to overcome the value-action gap (Burton et al 2008;Mills et al 2018). On the other hand, previous research shows there is a chance that focusing on economic gain changes farmers' decision-making from based on intrinsic motivations (wanting to do the 'right thing') to material factors (e.g.…”
Section: Implications For Designing Research and Extension Based On Tmentioning
confidence: 99%
“…Previous research investigating farmers' knowledge on soil functions across Europe and their demands for a decision support tool showed that not all farmers want the same kind of advice (Bampa et al, 2019). That study, in agreement with Mills et al (2018), concluded that farmer's motivations need to be taken into account to increase environmental benefits through management of agricultural landscapes. Bampa et al (2019) observed that farmers were generally highly interested in practical solutions and in access to high-quality information in conjunction with one-on-one personal communication with soil scientists, agronomists, and advisors.…”
Section: Future Prospects: Taking the Decision Support Model From Resmentioning
confidence: 54%
“…They have been found to be particularly useful in determining how specific attributes affect choices and can allow for estimation of the marginal rate of substitution (MRS) between attributes (Garrod, Ruto, Willis, & Powe, ; Greiner et al., ; Lancsar & Savage, ). Inclusion of information regarding farmers and farms allows for consideration of the heterogeneity in motivation and environmental behavior that is well documented in the literature (e.g., see Farmer, Ma, Drescher, Knackmuhs, & Dickinson, ; Mills et al., ; Sorice, Haider, Conner, & Ditton, ).…”
Section: Methodsmentioning
confidence: 99%
“…There is a considerable and growing body of literature that investigates how landowners, farmers, and ranchers make choices about participation in conservation programs, including those specifically targeted to restore or maintain wetlands (Kim & Petrolia, ; Pattison, Boxall, & Adamowicz, ; Schulz, Breustedt, & Latacz‐Lohmann, ; Welsh, Webb, & Langen, ; Yu & Belcher, ). In addition to financial incentives, farm characteristics, landowner and farmer characteristics, programs available, participant responsibilities and costs, farmer awareness and understanding of programs, access to information, conservation attitudes, presence of a succession plan, and experience managing wetlands, among others, have been identified as influencing adoption (Lesch & Wachenheim, ; Mills, Gaskell, Ingram, & Chaplin, ; Ribaudo, ).…”
Section: Introductionmentioning
confidence: 99%